(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This study examines the impact of telecommuting on work-life balance among bank employees in Delhi NCR. So, we chose 100 employees from banks like SBI and ICICI to write this paper. However, the online working mode changed their accountability, duties, tasks, and responsibilities at home and work. Moreover, the data were collected from a variety of sources and were collected while working online. It was collected via postal questionnaire and telephone interview using simple random sampling to ensure that all banking sectors were represented. Using ANOVA, we compared the difficulty of achieving work-life balance (WLB) in public and private sector banks. ANOVA was used to analyses the data, but also percentage and mean score. The ANOVA result shows that the obtained value is higher than the table value, rejecting the null hypothesis. It means that achieving WLB at different hierarchies is significantly more difficult. The study found that employees in the banking sector had increased workloads when working online. WLB is difficult to achieve when working online.